Aeroponic Spring Onion Monitoring System using IoT Platform - Momin, Gabriel Ruchie; Tasiransurini Ab Rahman (Evolution in Electrical and Electronic Engineering, 2024)
In the past decade, there has been a significant upswing in people’s curiosity about the origins of their food. A growing number of consumers now seek food that is not only considered "safe" but is also cultivated through sustainable and conscientious growing practices, free from pesticide residues. Aeroponics, a method of growing plants without soil in a misty environment using water vapor and an enriched nutrient solution, has emerged as a solution to achieve accelerated plant growth. However, the current aeroponics methods face a crucial challenge. They lack a monitoring system necessary for optimal plant growth. To overcome this problem, a comprehensive monitoring system was developed to monitor the temperature, humidity, water level, and pH sensor. These sensors were strategically chosen to measure the temperature and humidity of the plant surroundings, the water level of the nutrient solution, and the water pH condition. The parameters’ output is then displayed on both an LCD and the Blynk application, allowing users to observe and assess the plant conditions in real time. This versatile system accommodates the cultivation of plants indoors or outdoors, depending on the user’s preference. A five-week study was conducted, during which results were systematically collected.